Addendum to Aluminium [BAT value documentation, 2019]. Issue 4 (13th November 2019) - Klotz, K.; Meyer‐Baron, M.; van Thriel, C.; Pallapies, D.; Nasterlack, M.; Letzel, S.; Roßbach, B.; Triebig, G.; Weistenhöfer, W.; Drexler, H.; Hartwig, A.; ,
Abstract: In 2017, the German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the biological tolerance value (BAT value) for aluminium [7429‐90‐5 ]. Available publications are described in detail. The BAT value of 60 µg aluminium/g creatinine evaluated in 2009 was based on the linear correlation between external and internal exposure. The aim of this re‐evaluation was the derivation of a health‐based BAT value considering the most sensitive critical effect of aluminium, the neurotoxicity. For this purpose, the available studies of aluminium‐exposed workers were taken into account, when the internal aluminium exposure as well as the occurrence of subclinical neurotoxic effects were determined. The effects had been measured with standardised neuropsychological test procedures. From these studies, a no observed adverse effect level (NOAEL) of 50 µg/g creatinine for the occurrence of subtle neurotoxic effects of humans was estimated. Therefore, a BAT value of 50 µg aluminium/g creatinine was evaluated. Sampling time for long‐term exposures is at the end of the shift after several shifts.